THE ROLE OF TEACHING VOWEL SOUNDS IN PRONUNCIATION DEVELOPMENT - Nematullaeva , Muslimakhon Rakhmatullo kizi (GOLDEN BRAIN, 2024)
Teaching of vowel sounds plays a critical role in the development of pronunciation skills in language learners. This article explores the significance of vowel sounds in speech clarity and overall communication effectiveness. Drawing upon recent linguistic research, phonetic studies, and pedagogical approaches, how targeted vowel instruction can improve learners’ pronunciation, reduce foreign accents, and facilitate effective communication in a second language will be examined.